Relation between Cardiorespiratory Fitness Measured with Six-Minute Walk Test and Walking Speed Measured with 1— Meter Walk Test in Patients of Post-Subacute and Chronic Ischemic Stroke - Hening Laswati1, Cut Jaswanita Eka Putri1, Patricia Maria Kurniawati1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Cardiorespiratory fitness measurement using 6MWT (Six Minute Walking Test) and walking speed measurement using 10MWT (Ten Minute Walking Test) in post-stroke patients are measurement to assess post-ischemic stroke patients in subacute or chronic phase. This study is to assess cardiorespiratory fitness and to measure walking speed of post-stroke patients in subacute and chronic. We also aim to observe the relation between cardiorespiratory fitness and walking speed in post-stroke patients. Method: This study involved 38 subjects as samples. 6MWT assessment was conducted by measuring the mileage in six minutes. Walking speed was conducted afterwards with self-speed and fast-speed which were respectively assessed through three repetitions. Results: We found string correlation in 6MWT assessment results with mileage in meter and VO2 max (r = 0.680 and p = 0.000). The result of 6MWT measured with VO2 max (ml/kg/minute) indicated strong correlation with 10MWT both with self-speed (r = 0.715, p = 0.000) and fast-speed (r = 0.687 p = 0.000). Conclusions: We concluded that there was a relation between cardiorespiratory fitness and walking speed in post-subacute and chronic ischemic stroke patients.